Stochastic consensus of leader-following multi-agent systems under additive measurement noises and time-delays. (May 2015) - Djaidja, Sabir; Wu, QingHe
Abstract: Information exchange between agents in multi-agents systems is often inexact and delayed. This paper proposes a distributed leader-following consensus algorithm for continuous-time single-integrator multi-agent systems under measurement noises and time-delays in directed topologies. The information states received by an agent from its neighbors are delayed by uniform time-delays. In the meantime, they are corrupted by additive white noises. Based on graph theory and stochastic tools, conditions to ensure the tracking consensus in mean square for both directed fixed and switching topologies are derived. The effectiveness of the proposed algorithms is proved through some simulations.